ELEMENTARY STUDENTS DO LOVE SONG: Songs as Fun and Effective Media to Enhance Vocabulary Building for Elementary Students - Linna Endah Nur Wahyuni; Evi Uswatun Khasanah; Linna Endah Nur Wahyuni; Evi Uswatun Khasanah (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2025)
This study aims to describe how English Kids’ songs as media in teaching English to early childhood learners enhanced students’ vocabulary mastery. Considering young learners are naturally active, imaginative, and responsive to fun activities, songs become an appropriate approach to foster language interest and skills from an early age. The findings in this study revealed that English songs have been proven success in enhancing vocabulary for young learners. The catchy rhythms and repetitive lyrics help children memorize and imitate words within meaningful contexts, enrich children’s comprehension through audio/ audio visual context, cultural expressions, and simple verbal interactions that engage them actively. Observations, interview, and teacher reports indicated a significant increase in children’s interest of vocabulary mastery. The students’ vocabulary building is significantly improved when teachers play an active role in explaining the material, repeating key vocabulary, and facilitating interaction after the song is played. Therefore, it could be concluded that songs function not merely as entertainment but as meaningful, enjoyable, and effective tools in laying the foundation for English vocabulary at Islamic Elementary School, MI Unggulan Al Muhammad Cepu. Keywords: English Learning; Early Childhood; Educational Songs and Films.